Kualitas Susu Pasteurisasi Komersil - Zuraida Hanum; Veronica Wanniatie (Jurnal Agripet, 2015)
(The quality of commercial pasteurized milk)ABSTRACT. Pasteurized milk is processed milk through heating process at temperatures below its boiling point, therefore it still has the form and flavor of fresh milk. The quality of pasteurized milk is depend on the condition of processing and post pasteurization. Staphylococcus aureus is an indicator of milk hygiene. Ninety eight pasteurized milk samples from seven brands were collected in Jakarta and Bogor. Parameters observed were milk composition and the amount of Staphylococcus aureus in milk. The results showed that the pasteurized milk compositions (fat, protein and dry matter) were in accordance with the composition attached of the products label in SNI No.01-3951-1995 Moreover, we found that 71.4% of the samples containing Staphylococcus aureus above the milk quality standard ( 1.2 x 101 cfu/ml) according to SNI No. 01-6366-2000.